2021
DOI: 10.1186/s12902-021-00712-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin and mineral supplementation on women with gestational diabetes mellitus

Abstract: Background The effects of vitamin and mineral supplementation on women with gestational diabetes mellitus (GDM) have not been well established. We conduct a meta-analysis to evaluate the effects of vitamin and mineral supplementation on glycemic control, inflammation and oxidative stress for women with GDM. Methods A systematic search of randomized controlled trials (RCTs) was conducted from PubMed, Embase, Web of Science and Cochrane Library up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
1
9
0
3
Order By: Relevance
“…In addition, combined vitamin supplementation may also have an important role in glycaemic regulation in GDM. This is consistent with the findings of Li D et al (34) that combined vitamin supplementation significantly reduced blood glucose levels and maintained glycaemic homoeostasis in GDM patients. The reason for this may be that VA can indirectly reduce insulin resistance by regulating the level of the secreted adipokine RBP4 (35, 36) , while VE regulates the level of inflammation and oxidative stress in the body and reduces lipid peroxidation, which results in the regulation of glucose and insulin levels in the body (37) .In contrast, VD increases insulin sensitivity by activating vitamin D receptors in pancreatic β -cells (38) , while promoting an increase in glucose uptake in peripheral tissues and glycogen synthesis in the liver (39) , which allows blood glucose to become homoeostatic.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, combined vitamin supplementation may also have an important role in glycaemic regulation in GDM. This is consistent with the findings of Li D et al (34) that combined vitamin supplementation significantly reduced blood glucose levels and maintained glycaemic homoeostasis in GDM patients. The reason for this may be that VA can indirectly reduce insulin resistance by regulating the level of the secreted adipokine RBP4 (35, 36) , while VE regulates the level of inflammation and oxidative stress in the body and reduces lipid peroxidation, which results in the regulation of glucose and insulin levels in the body (37) .In contrast, VD increases insulin sensitivity by activating vitamin D receptors in pancreatic β -cells (38) , while promoting an increase in glucose uptake in peripheral tissues and glycogen synthesis in the liver (39) , which allows blood glucose to become homoeostatic.…”
Section: Discussionsupporting
confidence: 93%
“…Minerals are of paramount importance in order to preserve and obtain good health and their key role is supported by a significant amount of literature [ 3 ]. The crucial role of minerals shifts from helping vitamin absorption [ 4 ] and immunomodulatory effect [ 5 ] to metabolic [ 6 ] and bone metabolism [ 7 ], influencing hematological [ 8 ] and endocrine function [ 9 ]. The source of many important minerals is mainly plant-based therefore it is important to use a balanced diet to provide the adequate proportion of minerals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from studies on the general healthy population, the association of vitamin D and magnesium has also been assessed among pregnant women and the pediatric age group. A meta-analysis conducted by Li et al [ 48 ] evaluated the effects of vitamin and mineral supplementation on glycemic control for women with GDM. Their findings showed that 100 mg magnesium plus 200 IU vitamin D supplementation twice a day causes a significant decrease in the FPG and HOMA-IR levels.…”
Section: Association Of Vitamin D and Magnesium In Insulin Sensitivit...mentioning
confidence: 99%